L'Afrique et la fin de la guerre froide : de la nécessité d'un « nouveau réalisme » - Kühne, Winrich (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1991)
Superpower disinterest turns out to be the main feature of Africa's post cold war era. Although marxism-leninism and models of socialist orientation based thereupon have utterly failed, there is not much reason for capitalism to triumph either: the debate on the limits and risks of the market forces will continue as the example of South Africa shows. The eighties have turned out to be a lost decade for development in Africa and there will be no significant rise in outside development assistance in the coming years : expectations for a Marshall Plan for Africa and hopes concerning a "peace-dividend" because of disarmament in Europe should be discounted in the context of the exploding cost of European reconstruction. Africans can either react with despair or with a "New Realism", geared at solving their problems essentially by mobilising their own resources and creativity. Europe, for its part, would be ill-advised to judge its relations with Africa merely in terms of diminishing strategic and economic interests.